Personal protective equipment simulation training is associated with lower COVID-19 infection among healthcare workers - Thomaz Bittencourt Couto; Paula Dias de Toledo Rodovalho Menezes; Joyce Kelly Barreto Silva; Priscilla Cerullo Hashimoto; Euma Ferreira de Sousa; Selma Tavares Valério; Etienne Larissa Duim; Simone Cristina Azevedo Silva; Lívia Almeida Dutra; Claudia Szlejf (Einstein (São Paulo), 2023)
ABSTRACT Objective To describe the personal protective equipment training strategies during the beginning of the pandemic and to investigate the association between training and COVID-19 infection among healthcare workers. Methods This cross-sectional study conducted between March and May 2020 included 7,142 healthcare professionals who were eligible for both online and face-to-face simulation-based training on personal protective equipment use. Simulation training attendance was assessed by reviewing the attendance list, and the COVID-19 sick leave records recovered from the institutional RT-PCR database used to grant sick leave. The association between personal protective equipment training and COVID-19 was investigated using logistic regression, adjusted for sociodemographic and occupational characteristics. Results The mean age was 36.9 years (± 8.3), and 72.6% of participants were female. A total of 5,502 (77.0%) professionals were trained: 3,012 (54.7%) through online training, 691 (12.6%) through face-to-face training, and 1,799 (32.7%) through both strategies. During the study period, 584 (8.2%) COVID-19 cases were diagnosed among these professionals. The number of positive RT-PCR tests was 180 (11.0%) for untrained professionals, 245 (8.1%) for those trained only online, 35 (5.1%) for those trained face-to-face, and 124 (6.9%) for those trained with both strategies (p<0.001). Participants who received face-to-face training had a 0.43 lower risk of contracting COVID-19. Conclusion Personal protective equipment training decreased the odds of COVID-19 among healthcare professionals, with face-to-face simulation-based training being most effective.